Conceptualising and Measuring the Mobility of Indigenous Students in the Northern Territory - Taylor, Andrew; Dunn, Bruce (The Australian Journal of Indigenous Education, 2010)
Abstract The vexed and ongoing issue of poor educational outcomes for Indigenous students in the Northern Territory continues despite years of successive programs and policies. Much of the debate has been on funding and pedagogy, in particular the merits or otherwise of bi-lingual teaching. Largely omitted from discussions, although well known by teachers and schools in remote areas to be an issue, are high rates of in-term student mobility. Such “unexpected” moves are thought to affect the capacity for students to achieve benchmark outcomes, for teachers to deliver these and for schools to administer their students within the allocated systems and budgets. Up to now teachers and schools have relied on anecdotes to engage in dialogue around the impacts of mobility. This is because adequate conceptualisations for aggregating, depicting and reporting on the size and nature of in-term mobility were not available. This paper documents several years of work into producing these outcomes. Three measures are conceptualised and outlined in this paper which will be of interest to teachers, schools and educational administrators in all jurisdictions where services are delivered in a remote setting. The results clearly demonstrate the high churn of Indigenous students within terms, especially in remote areas of the Northern Territory. The findings from this study can be applied to inform funding and policy making and as a basis for further research to document the impacts for teachers and schools.